Exports, energy and the environment in China: an input-output perspective. (1st January 2012) - Shi, Yutian; Sharma, Kishor; Murphy, Tom; Hicks, John; Arthur, Lesley
This paper investigates how the changing structure of Chinese foreign trade has impacted on employment, energy-intensity and the environment in recent years. Our findings indicate a considerable fall in both employment and energy intensity. A fall in employment intensity appears to be mainly due to an increase in the exports of assembly items which are relatively less unskilled employment intensive, while a decline in energy consumption, per billion yuan worth of exports, appears to be due to increased use of energy saving technology as the price of energy rises and the pressure for improving Chinese environmental standards grows. While a fall in energy consumption is a welcome development, overall environmental standards in China remain a major concern, not only for the Chinese but globally. The paper also suggests that increased investment in human capital is part of the answer to increasing employment in the modern economy while minimising damage to the environment. In turn increased human capital may see decreased reliance on exports to drive employment growth which would help rebalance trade between China and the rest of the world.